More Slack than Meets the Eye? : Recent Wage Dynamics in Advanced Economies - Hong, Gee Hee (IMF Working Papers; Working Paper ;, 2018)
Nominal wage growth in most advanced economies remains markedly lower than it was before the Great Recession of 2008-09. This paper finds that the bulk of the wage slowdown is accounted for by labor market slack, inflation expectations, and trend productivity growth. In particular, there appears to be greater slack than meets the eye. Involuntary part-time employment appears to have weakened wage growth even in economies where headline unemployment rates are now at, or below, their averages in the years leading up to the recession.